Opprør og opposisjon under enevelde og demokrati - Seland, Bjørg (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"This book addresses political conflicts in Norway through an extended time span, from the late autocracy of the 18th century until the democratic challenges of today. The book holds eight articles focusing on historical phases which have been particularly influenced by social and political mobilization. Thus, the book traces an oppositional tradition across borders in time and space. Although the articles are based on limited studies, the authors write with ambition to include their research into this wider context. In Norway, the Constitution of 1814 marks the shift from autocratic rule to early democracy. 18th century peasant riots may be interpreted as expressions of impotence of the common people, but also as an opportunity for action with the potential to influence the authorities. The 19th century peasant opposition shows the potential for change through parliamentary representation. Around 1850 the first attempts at worker's organizations were criminalized - around 1950, however, the Labour Party dominated Norwegian politics. These trending lines reflect an increasingly developed democracy. The political system is in principle opening for broad popular participation. However, democracy is still being challenged by opposition in ways and by means that occasionally raise concerns about the stability of our political culture. The book is divided into three parts. Part I is dedicated to the age of late autocracy, part II provides insights into the 19th century democratization processes, while Part III includes articles dealing with opposition and confrontations in the last century, focusing the interwar period, the 1970s, and today's multicultural society.The book is aimed both at researchers, students and the general audience."